2016
DOI: 10.1002/adhm.201600159
|View full text |Cite
|
Sign up to set email alerts
|

Phase and Size Control of Core–Shell Upconversion Nanocrystals Light up Deep Dual Luminescence Imaging and CT In Vivo

Abstract: Upconversion nanocrystals (UCNCs) have recently been explored as optical imaging nanoprobes. However, conventional β-NaLuF4 (-) based UCNCs often suffer from large particle size and weak upconversion luminescence (UCL) intensity, leading to poor biocompatibility and low detection sensitivity. Here, a novel strategy for controlling the crystalline phase and size of UCNCs has been developed by doping of yttrium ions, resulting in particle size reduction and phase transition. The total UCL intensity of prepared c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…It is well known that multifunctional nanocomplexes have attracted great attention in biomedical fields because of their combined features of diagnostic sensing and therapeutic functions within a single platform. The simple synthesis procedures and commercially available raw materials for various nanocomplexes, including Janus particles, core/shell nanoparticles (NPs), and element-doped NPs have further stimulated the development of theranostic nanomedicine due to facilitated clinical translation. To date, a large number of theranostic agents have been created by combining diagnostic functions such as magnetic resonance imaging (MRI), photoacoustic imaging (PA), and X-ray computed tomography (CT) with therapeutic roles such as radiotherapy, chemotherapy, and photothermal therapy (PTT) for potential applications in the treatment of cancer or other diseases. Nanocomplexes with MRI and PTT functions have especially drawn much attention for their intrinsic characteristics that combine high spatial resolution, noninvasiveness, and three-dimensional images of MRI, and the noninvasiveness, low number of side effects, high efficiency, and selectivity of PTT. …”
Section: Introductionmentioning
confidence: 99%
“…It is well known that multifunctional nanocomplexes have attracted great attention in biomedical fields because of their combined features of diagnostic sensing and therapeutic functions within a single platform. The simple synthesis procedures and commercially available raw materials for various nanocomplexes, including Janus particles, core/shell nanoparticles (NPs), and element-doped NPs have further stimulated the development of theranostic nanomedicine due to facilitated clinical translation. To date, a large number of theranostic agents have been created by combining diagnostic functions such as magnetic resonance imaging (MRI), photoacoustic imaging (PA), and X-ray computed tomography (CT) with therapeutic roles such as radiotherapy, chemotherapy, and photothermal therapy (PTT) for potential applications in the treatment of cancer or other diseases. Nanocomplexes with MRI and PTT functions have especially drawn much attention for their intrinsic characteristics that combine high spatial resolution, noninvasiveness, and three-dimensional images of MRI, and the noninvasiveness, low number of side effects, high efficiency, and selectivity of PTT. …”
Section: Introductionmentioning
confidence: 99%
“…It has been previously shown that light within the near infrared (NIR) window (650 - 900 nm) exhibited greatest tissue penetration capability 10 . Consequently, tissue-penetrable NIR-sensitive dyes are often utilized as the photo-responsive agents to generate effects of hyperthermia 11 - 14 , photoacoustics 15 , 16 or photoluminescence 17 within the whole tumor region.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1,2 ] It relies on advanced medical imaging technique, fusion of multimodality medical imaging, and information on medical cases. [ 3–5 ] Among the common imaging modes, magnetic resonance imaging (MRI) has high spatial resolution but low sensitivity, whereas fluorescence imaging (FI) has high sensitivity but limited depth of penetration. [ 6–8 ] The combination of these two imaging technologies leads to complementary advantages.…”
Section: Introductionmentioning
confidence: 99%